Potential Analysis of Natural Stone Mining Activities in Mount Kuda on Environmental Quality as SDGs-Based Science Teaching Material - Dede Cahyati Sahrir; Margareta Rahayuningsih; Aditya Marianti (Journal of Environmental and Science Education, 2024)
The Gunung Kuda mining area in the Cipanas Village area, Dukupuntang District, Kuningan Regency has the potential for natural resources as a type of C excavation mine with a limestone soil texture where the results are partly used as raw materials for cement, natural stone and ceramics. The aim of this research is to examine the impact of Gunung Kuda mining activities on environmental quality as a source of SDGs-based science learning. The research method used is descriptive qualitative. Data collection techniques were carried out using open interviews, field observations and literature reviews. The results obtained show that Mount Kuda mining activities have positive and negative impacts. The positive impact felt by the surrounding community is as a center of livelihood to stabilize the economy. However, there are also negative impacts in the form of decreasing the quality of the surrounding environment, such as the river in the Gunung Kuda mining area which is classified as moderately polluted, namely with a value of Plj 10.39; air pollution in the form of dust resulting from the breakdown of rocks; as well as reduced vegetation in mining areas. Efforts made by the management and surrounding communities to balance the environment in the mining area are by replanting trees that have been reduced due to the mining process with trees that are considered to have benefits such as mango trees, durian trees and sengon trees. The results of the analysis of the impact of Mount Kuda mining on environmental quality are suitable as a study in SDGs-based contextual science learning resources.